2023
DOI: 10.3390/antiox12040932
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Protein Serum Concentration in Human CKD Shows a Biphasic Behavior

Abstract: Oxidative stress contributes to the progression of chronic kidney disease (CKD) and CKD-related mortality. The nuclear factor erythroid 2-related factor 2 (Nrf2) is essential in the regulation of cellular redox status, and Nrf2-activating therapies are under evaluation in several chronic diseases, including CKD. It is therefore inevitable to understand how Nrf2 behaves in advancing CKD. We analyzed Nrf2 protein concentrations in patients with varying extents of CKD but without renal replacement therapy, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Autophagia is important for the clearance of damaged proteins and organelles, and thus the prevention of inflammation ( 106 ). Inflammation has been proposed as being a prominent feature of CKD ( 45 , 108 , 109 ). Treatment with SGLT2 inhibitors may contribute to increased autophagia, decreased inflammation and thereby prevent fibrosis through their actions regarding ketone bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagia is important for the clearance of damaged proteins and organelles, and thus the prevention of inflammation ( 106 ). Inflammation has been proposed as being a prominent feature of CKD ( 45 , 108 , 109 ). Treatment with SGLT2 inhibitors may contribute to increased autophagia, decreased inflammation and thereby prevent fibrosis through their actions regarding ketone bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Robust activation of NRF2 is observed in the earlier stages of CKD development along with inflammation. In contrast, advanced CKD has been associated with the repression of the NRF2 pathway [ 101 ]. A patient-based study conducted by Rasmussen et al reported a biphasic pattern of NRF2 concentration in CKD wherein low glomerular filtration rates were associated with lower NRF2 protein concentration [ 101 ].…”
Section: Mitochondrial Function In Normal Renal Metabolismmentioning
confidence: 99%
“…In contrast, advanced CKD has been associated with the repression of the NRF2 pathway [ 101 ]. A patient-based study conducted by Rasmussen et al reported a biphasic pattern of NRF2 concentration in CKD wherein low glomerular filtration rates were associated with lower NRF2 protein concentration [ 101 ]. The study reported increased NRF2 protein levels in mild to moderate kidney function impairment, and the downregulation of NRF2 was observed in severe renal impairment [ 101 ].…”
Section: Mitochondrial Function In Normal Renal Metabolismmentioning
confidence: 99%
“…Furthermore, Nrf2 inducers have been shown to have anti-inflammatory, antioxidant, and protective effects against renal injury in LN mice ( 4 ). Currently, clinical studies on Nrf2 have focused on advanced kidney disease, with reports indicating that Nrf2 expression correlated with the degree of renal failure and comorbidities ( 8 , 9 ) and Nrf2 expression varied among different types of immune cells and tissues ( 4 ). Meanwhile, regarding clinical trials, it was noted that the Nrf2 activator bardoxolone methyl did not reduce the risk of death due to ESRD in patients with type 2 diabetes and stage 4 chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…It led to a higher rate of cardiovascular events compared to the placebo group, leading to the termination of the trial ( 10 ), as this Nrf2 activator resulted in an increased albuminuria ( 10 , 11 ). This necessitates the exploration of a uniform assay for Nrf2 protein levels and clinical evaluation of targeted Nrf2 therapy for renal disease ( 9 ). This makes it challenging to assess Nrf2 levels and administer interventions targeting Nrf2 in human LN cases.…”
Section: Introductionmentioning
confidence: 99%